Armenian identity and migration: notes and criticals - Camarero, Artur Attarian Cardoso (Geografares, 2019)
The aim of this paper is to present the interpretations about the problem of Armenian identity and its unfolding as an international social relation in the destinies of the so-called Armenian diaspora and in Armenia, endowed with various forms of representation conceived from the concept of labour mobility (Gaudemar, 1997) to criticize the culturalist understanding of the problem. The text closes with some critical reflections about our work field experience carried out in Armenia in the second half of 2016 under the critical perspective of value-dissociation, in dialogue with Scholz (2016), to think about the so-called “women’s issue” in this country.
Keywords: labor mobility; Armenian identity and accumulation crisis.; Armenia